Effects of the coating and calcium application on the quality and shelf life of radishes - Tulin Ayse O.Z.; Eryol Busra (Journal on Processing and Energy in Agriculture, 2019)
Local Kadirli radises were harvested and divided into four different groups. The crops were selected according to their uniformity, and then cut manually using a sharp knife. Treatments with 1% calcium chloride, 1% chitosan coating and 1% calcium chloride + 1% chitosan coating were applied to the fresh-cut radish slice samples and stored in a polypropylene box at 0° C in the 90% relative humidity for 12 days. The treated fresh-cut radish samples were analyzed for mass loss, firmness, ethylene production, color (Chroma), sensory analysis, chemical (TSS, pH), microbiological and E.C. membrane integrity for 3-day intervals during storage. When the data obtained from the study were evaluated, it was determined that the calcium chloride application had significant effects on the mass loss (%) and firmness (N) of the samples examined, whereas CaCI2 exerted a significant impact on the firmness and E.C. (%) membrane integrity of the samples examined. According to the results of microbiological analysis, the chitosan application was found to exert a notabe effect on the development of total aerobic bacteria.